Digital Marketing: Paid Internet Advertising and Its Revenue Model (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
This review paper has explored literature review of 18 research papers and review papers to understand the various types of digital marketing techniques and the existing literature on their performance indicators which are used to develop a revenue model. The research shows the rise of digital media and has helped understand various aspects of customer engagement, which is helping the brands improve their marketing strategies, increase their presence and revenue in the market. The past decade has seen the rise of digital marketing strategies, but there is still a lot of research scope to identify models to measure the effectiveness of each strategy and identify an optimal level of investment in digital marketing techniques. Another area of research that is currently catching the attention of the business houses is the increasing involvement of government regulations and policies to govern the e-commerce segment, social media marketing and even the fintech world of cryptocurrency.